Otaku Company / Pg Khairul Azri Pg Ahmad ... [et al.] - Pg Ahmad, Pg Khairul Azri; Amin, Bibi Nurnashiha; Izaie, Nur Farahin; Ismail, Shahrul Eqwan; Moksan, Shahrul Rezza; Musleh, Nur Safiana (2013)
Assalamualaikum wbt, first of all, we would like to give a big of applause for our members, it is because after the long term brainstorming without any negative criticize, a good commitment between us, and always generating others ideas finally we have came out with a certain of business services project, which is a theme park indoor that will use the Japanese animation (anime) theme and the name of our company is "Otaku Club.Sdn.Bhd". Our business is based on partnership which includes 6 persons of our members who have certain qualification and experience work in business management at the several company in our country. As related, our company name "Otaku" is derived from the Japanese term that is means a persons that obsessing in something. In Japanese nowadays the word of otaku is officially use to call a persons who are fanatic with the animation world. For example the persons who interpret the culture, manga collector, games etc. We have chosen to open the business as a fact that nowadays the otaku virus has been refuse to our country. This is also our main purposes of existing the anime theme park indoor which also a kind of fun services that are prepared to our people that are fans and, the people want to know a lot about anime culture. Our company provided a lot of fun and variety in the otaku club, such as, we prepared a costume of anime for the visitor, boots , mini cinema, games, house of animae, character statue and much more. We chosen the fun and variety based on what did have in anime that relate to the people love. Furthermore, our company destinations are located around Kota Kinabalu at One Borneo, Jalan Sulaman at 1st & 2nd floor and our business operates from 9.00 a.m to 9.00 p.m. The most important is that our business is the first ever served the fun service of animae theme park indoor.